Figures of Comparison in the Novel Anak Perawan di Sarang Penyamun by Sutan Takdir Alisjahbana as Literature Teaching Material - Rosa Dalima Bunga; Hawiah Djumadin (The Future of Education Journal, 2024)
The problem in the research is what is the comparative language style in the novel Anak Perawan di Sarang Penyamun by Sutan Takdir Alisjahbana. The aim is to describe the comparative language style in the novel Anak Perawan di Sarang Penyamun by Sutan Takdir Alisjahbana. Descriptive qualitative research aims to reveal various qualitative information. The method used in this research is a qualitative descriptive method. The data used in the research are sentences containing comparative figures of speech. Data source for the novel Anak Perawan di Sarang Penyamun by Sutan Takdir Alisjahbana. The technique used is literature study. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the research show that there is a comparative language style consisting of personification figures of speech, allegory figures of speech, and hyperbole figures of speech. The three figures of speech found can be used as teaching materials in literature learning specifically on the main material of novel texts and basic competency 3.4 analyzing the content and language of novels.